Women’s Participation in Coastal Community Empowerment Programs - Zidna Azzahra; Sugiarso Sugiarso (Prosperity: Journal of Society and Empowerment, 2022)
Karangasem Utara Urban Village is one of several urban villages located in the coastal area of Batang Regency, and is active in implementing community empowerment programs. In this case, there is community participation, and there are still different perceptions between individuals regarding domination and the division of labor based on gender. Therefore, this study aims to analyze more deeply how the concept of gender equality is in the coastal community empowerment program in Karangasem Utara Urban Village. This study applies a qualitative method with a phenomenological approach that utilizes primary data obtained from interviews and observations and secondary data obtained from the documentation. The results of this study indicate that first, community empowerment programs in Karangasem Utara Urban Village are the “Pelatihan Pemberdayaan” and the “Kelompok Usaha Bersama (KUB).” Second, women and men have equal rights in access and control of community empowerment programs, namely in the planning, implementation, and evaluation processes. Third, there are several factors that cause women’s passive participation in community empowerment programs in Karangasem Utara Urban Village.